Interface design of low-frequency band gap characteristics in stepped hybrid phononic crystals. (November 2021) - Guo, J.C.; Li, J.R.; Zhang, Z.
Abstract: A stepped hybrid frame-pillar phononic crystals (PnCs) is designed for the reduction of vibrations in wide low-frequency ranges. The interface effect on band gap characteristics is further studied. In comparison with the traditional PnCs, the proposed frame-pillar PnCs produce an entire extremely low frequency complete wide band gap. With the variation of the interface property, the starting frequency of the designed frame-pillar PnCs can be reduced to be 1/6 of the first band gap starting frequency of the traditional tapered plate PnCs. The interface property, as well as the geometrical parameters, constitutes of the main design factors of PnCs to adjust the band gap characteristics in the extremely wide range of frequency. Moreover, the single sided frame-pillar PnCs and the single sided plate-pillar PnCs of AlSi10Mg were fabricated by Selective Laser Melting (SLM) additive manufacturing technology. The bandgap characteristics of the SLM components show that the interface connection takes key role in the design of the stepped hybrid frame-pillar PnCs.